2004
DOI: 10.1097/00007691-200412000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Overview of FTY720 Clinical Pharmacokinetics and Pharmacology

Abstract: Drug discovery programs are actively exploring for therapeutic agents targeting enzymes and receptors regulating sphingolipid metabolism and biologic functions. FTY720 is a close structural analogue of sphingosine with immunomodulatory properties. After oral administration, FTY720 is phosphorylated by sphingosine kinase to form the active moiety FTY720-phosphate, which subsequently binds to the sphingosine-1-phosphate receptor. In characterizing the safety and pharmacological effects of FTY720, detailed clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 11 publications
5
63
1
Order By: Relevance
“…Therefore, administration of 10 mg/kg FTY720 would be expected to result in a concentration of approximately 1 M of FTY720 and phospho-FTY720. Similar results were reported in humans administered 5 mg/kg FTY720 for 7 days (Kovarik et al, 2004). These data showed that administration of FTY720 produced equal levels of FTY720 and phospho-FTY720 in the blood over the 24-h period monitored after drug administration.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, administration of 10 mg/kg FTY720 would be expected to result in a concentration of approximately 1 M of FTY720 and phospho-FTY720. Similar results were reported in humans administered 5 mg/kg FTY720 for 7 days (Kovarik et al, 2004). These data showed that administration of FTY720 produced equal levels of FTY720 and phospho-FTY720 in the blood over the 24-h period monitored after drug administration.…”
Section: Discussionsupporting
confidence: 87%
“…37 ).The S1P analog FTY-720 is a functional antagonist of S1P activity as it binds to and downregulates expression of S1P receptors ( 38 ). These results in a transient, ‫ف‬ 40% decrease in peripheral blood lymphocyte counts ( 39 ). In this report, we have also shown that treatment of mice with anti-S1P mAbs transiently depletes peripheral blood lymphocytes in a fashion similar to that observed with FTY-720.…”
Section: Anti-s1p Mabssupporting
confidence: 62%
“…20 This compound shows few toxic effects in either animal or human studies. 21,22 Accordingly, no adverse effects or significant changes in body weight were observed in the present investigation in treated animals during the FTY720-application period. Because of rapid initial absorption (time of occurrence for maximum drug concentration Ϸ2 to 24 hours), extensive volume of distribution, and exceptionally long elimination half-life (Ϸ7 days), FTY720 blood concentrations remain stable after administration, with little fluctuation during the dosing interval.…”
Section: Fty720 Determination Application and Distributionmentioning
confidence: 48%
“…Because of rapid initial absorption (time of occurrence for maximum drug concentration Ϸ2 to 24 hours), extensive volume of distribution, and exceptionally long elimination half-life (Ϸ7 days), FTY720 blood concentrations remain stable after administration, with little fluctuation during the dosing interval. [21][22][23] Consistent with these pharmacokinetic properties, twice-or thrice-weekly administration of FTY720 is sufficient to suppress inflammatory processes in various mouse models. 24,25 In the present study, we found that repeated intraperitoneal injection of the compound (20 g/LDL-R Ϫ/Ϫ mouse, thrice weekly) produces FTY720 plasma concentrations of 67.5Ϯ8.7 ng/mL, which is within the known therapeutic concentration range.…”
Section: Fty720 Determination Application and Distributionmentioning
confidence: 84%